Impact of the introduction of a specialist critical care pharmacist on the level of pharmaceutical care provided to the critical care unit. (18th January 2016) - Richter, Anja; Bates, Ian; Thacker, Meera; Jani, Yogini; O'Farrell, Bryan; Edwards, Caroline; Taylor, Helen; Shulman, Rob
Abstract: Objectives: To evaluate the impact of a dedicated specialist critical care pharmacist service on patient care at a UK critical care unit (CCU). Methods: Pharmacist intervention data was collected in two phases. Phase 1 was with the provision of a non-specialist pharmacist chart review service and Phase 2 was after the introduction of a specialist dedicated pharmacy service. Two CCUs with established critical care pharmacist services were used as controls. The impact of pharmacist interventions on optimising drug therapy or preventing harm from medication errors was rated on a 4-point scale. Key findings: There was an increase in the mean daily rate of pharmacist interventions after the introduction of the specialist critical care pharmacist (5.45 versus 2.69 per day, P < 0.0005). The critical care pharmacist intervened on more medication errors preventing potential harm and optimised more medications. There was no significant change to intervention rates at the control sites. Across all study sites the majority of pharmacist interventions were graded to have at least moderate impact on patient care. Conclusion: The introduction of a specialist critical care pharmacist resulted in an increased rate of pharmacist interventions compared to a non-specialist pharmacist service thus improving the quality of patient care.